Stochastic Optimal Control by Pseudo-Inverse - Basu, Dipak R.; Lazaridis, Alexis (The Review of Economics and Statistics, 1983)
Also, I investigated various proxies for labor intensity other than average work-week, compared three methods of deseasonalization, tested the model with monthly and quarterly data, and tested the ability to forecast using models A and B. results of each of these inquiries are available from the author upon request. (Palo Alto, California: Stanford University Press, 1959). Berndt, Ernst R., Melvyn A. Fuss, and Leonard Waverman, Dynamic Adjustment Models of Industrial Energy Demands: Empirical A nalysis for U. S. Manufacturing 1947-1974 (Palo Alto, California: Electric Power Research Institute, 1980). Morrison, Catherine J., and Ernst R. Berndt, Short-Run Labor Productivity in a Dynamic Model, Journal of Econometrics 16 (Aug. 1981), 339-365. Nadiri, M. Ishaq, and Sherwin Rosen, Interrelated Factor Demand Functions, American Economic Review 59 (Sept. 1969), 457-471. , A Disequilibrium Model of Demand for Factors of Production (New York: National Bureau of Economic Research, 1974). Tinsley, P. A., An Application of Variable Weight Distributed Lags, Journal of the American Statistical Association 62 (Dec. 1967), 1277-1289. Treadway, Arthur B., The Globally Optimal Flexible Accelerator, Journal of Economic Theory 7 (1974), 17-39.